The effect of different stretching protocols on vertical jump measures in college age gymnasts - Montalvo, S.; Dorgo, S. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Gymnastics is a sport that requires rapid display of explosive power expressed through the vertical jump. Recent studies have shown that a static-stretching based warm-up is ineffective for explosive power development. The aim of this study was to compare different stretching protocols and their effect on vertical jump measures. METHODS: Eleven gymnasts (9 males, 2 females; 23.18±2.52 yrs) participated in this randomized crossover study. Participants were measured on the countermovement jump (CMJ), squat jump (SQJ), and depth jump (DJ) at baseline (no warm-up). Participants were then randomly placed into one of four stretching protocols: Static (ST), dynamic (DY), static + dynamic (ST+DY), and dynamic + static (DY+ST) and tested on the CMJ, SQJ, and DJ. A photoelectric cell device was used to measure vertical jump height (VJH), flight time (FT), power output (PO), and Reactive Strength Index (RSI). The non-parametric Friedman test was used to test differences between stretching protocols. RESULTS: The DY protocol showed significant improvements in VJH, FT, and PO in the CMJ. The ST, ST+DY, and DY+ST protocols did not show any significant improvements. CONCLUSIONS: A warm-up consisting of dynamic movements that resemble those used in the sport of gymnastics can improve vertical jump measures, as reflected through the CMJ.